Boswellia occulta (Burseraceae), a new species of frankincense tree from Somalia (Somaliland) - Thulin, Mats; Decarlo, Anjanette; Johnson, Stephen P. (Phytotaxa, 2019)
The new species Boswellia occulta is described from a small area in the Ceel Afweyn District of Somaliland (northwestern Somalia), where it is locally of considerable socio-economic importance. Although used for frankincense production by many generations of local harvesters, it has been unknown to science until now. Apart from the recently collected type material, it is also known from a sterile and hitherto misunderstood collection made in 1945. The simple-leaved Boswellia occulta is morphologically compared with B. sacra and B. frereana, the two major frankincense-producing species in the region, both with imparipinnate leaves, and it appears to be most closely related to B. sacra. The new species is the only simple-leaved species of Boswellia known outside Socotra.